The Effect of s Higher Education on the Human Capital Quality - Siti Patimah (Ar-Raniry: International Journal of Islamic Studies, 2014)
Higher education has a very strategic position to determine the quality of human capital. Therefore, a higher education must always strive to provide quality assurance services to the interested parties. The more quality customer service is given, the more college customer will satiesfied that have an impact on the increasing investment of the human resources (Human Capital).